Patellofemoral syndrome: Diagnostic pointers and individualized treatment - Labotz, M. (The Physician and Sportsmedicine, 2004)
Most patients who have patellofemoral syndrome can be successfully treated once contributing factors are identified during history taking and physical examination. After pain and inflammation are treated, patients are encouraged to start activities that do not provoke pain. Exercise programs should be implemented that address underlying strength and flexibility deficits. Return to play primarily relies on advancement of pain-free activity, with some allowance for patients' competitive goals. Patients remaining symptomatic after compliance with a structured rehabilitation program or those with indicators of other intra-articular pathology should be referred to an orthopedist.